Analysis of Financial Performance Development Based on EVA Approach and Profitability Ratio at Barokah Village Unit Cooperative in Karya Mukti Village, Subdistrict Maro Sebo Ilir - Muryati Muryati; Ahkmadi Ahkmadi (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
The development of financial position had a very important meaning for the company. The important factor to see development of the company was the financial element, because that can evaluate the capability of the company is correct or not. The purpose of this research was to know the development of the financial performance based on EVA approach and profitability ratio at Barokah Village Unit Cooperative in Karya Mukti Village, subdistrict Maro Sebo Ilir. The problem’s formulation from this research was how is the development of the financial performance based on EVA approach and profitability ratio at Barokah Village Unit Cooperative in Karya Mukti Village, subdistrict Maro Sebo Ilir. The type of data used in this research was primary and secondary data from Barokah Village Unit Cooperative in Karya Mukti Village, subdistrict Maro Sebo Ilir. The method of this research was descriptive quantitative method and using EVA and profitability ratio analysis. The result of the research based on EVA approach and profitability ratio was financial performance at Barokah Village Unit Cooperative based on NOPAT/SHU Income, Invested Capital, WACC, Capital Charges and EVA was good. Financial performance based on ROI was not too good and based on ROE was good. Financial performance based on EVA approach have a good average value, but must be kept in order to get a better value. Financial performance based on profitability ratio especially ROI was not good, so it must be improved in order to get a good value.